Micronutrients:Their behavior in Soils and Plants - Dilip Kumar Das; Dilip Kumar Das (Ludhiana New Delhi, 2007)
This text book is a comprehensive one and will meet the growing need of students studying agricultureand other related fields.
copper and zinc boron molybdenum micronutrients pollution.
Keywords: copper and zinc, boron, molybdenum